Highly conductive epitaxial β-Ga2O3 and β-(AlxGa1−x)2O3 films by MOCVD. (1st October 2022) - Alema, Fikadu; Itoh, Takeki; Vogt, Samuel; Speck, James S.; Osinsky, Andrei
Abstract: We report on the epitaxial growth of highly conductive degenerated Ge or Si doped β -Ga2 O3 and β -(Al x Ga1− x )2 O3 films by MOCVD. Highly conductive homoepitaxial β -Ga2 O3 layers with record conductivities of 2523 and 1581 S cm −1 were realized using Si and Ge dopants. Highly conductive Si doped β -(Al x Ga1− x )2 O3 films were also grown. The incorporation of Si decreased with the increase in Al content and layer thickness. Record high conductivity of 612 S cm −1 was attained for coherently strained β -(Al0.12 Ga0.88 )2 O3 .